A three-stage approach for co-designing diversified cropping systems with farmers: the case study of lentil-wheat intercropping - Leoni, Federico; Carlesi, Stefano; Triacca, Alessandro; Koskey, Gilbert; Croceri, Gilberto; Antichi, Daniele; Moonen, Anna-Camilla (Italian Journal of Agronomy, 2023)
There is an increasing need for more sustainable and diversified cropping systems while guaranteeing adequate crop yields and economic viability for European farms. The intercropping of lentils with wheat can be a valuable agroecological practice for stabilizing crop yields and improving weed control; however, this requires better knowledge about the technical viability, suitable varieties, sowing density, management practices for different conditions, and the feasibility of these solutions for farmers. In this paper, we present a three-stage participatory approach aimed at involving farmers in the evaluation and design of knowledgeintensive agroecological cropping systems and apply it to the case of wheat-lentil intercropping. The proposed approach is articulated into three connected stages involving experiments at different scales (plot, field, and farm) and with different grades of interactions among farmers and researchers regarding the design of experiments and the evaluation of the results. In the first stage, we set up controlled plot experiments at an experimental station allowing all interested farmers to observe and comment on the various treatments that were investigated during dedicated events. This stage tested the potential of intercropping to improve the sustainability of the local farming system and provide a solid scientific background to the ecosystem services provided by wheatlentil intercropping, such as crop production, yield stability, and weed control. While being agronomically beneficial, the technical feasibility and economic benefits of wheat-lentil intercropping have yet to be proven. Therefore, based on the results obtained from the first stage and the feedback of local farmers on the opportunities and weaknesses of the on-station application of wheatlentil intercropping, a second experiment was carried out using commercial agriculture machines to test the technical viability of intercropping at a larger scale. In the final third stage, we set up a co-designed on-farm experiment aimed at supporting a farmer in establishing lentil-wheat intercropping adapted to the farm conditions. This approach demonstrated that gradually involving farmers in the experimental process, starting from evaluating the most promising agroecological solutions on station to implementing them on farms, supports a successful agroecological transition of farms towards more diversified cropping systems.